KOHESI LEKSIKALI DALAM LIRIK LAGU CRAIG DAVID - Hutahaean, Sorta; Edward, Edward (Universitas Lancang Kuning, 2015)
The purpose of this analysis is to describe the lexical cohesion in five Craig David song lyrics. The data were taken from the words, phrases, sentences of the song lyrics which contain the elements of lexical cohesion. Lexical cohesion described are repetition, synonymy, antonymy, equivalent, hyponymy, metonymy, and collocation. Data analysis is descriptive qualitative. The analysis is based on the semantic relation. The lexical cohesion in the lyrics are supported by the cohesiveness of the text. The aims of using lexical cohesion is to make the text harmony and to tie the text in order to have contextual meaning. The finding shows that repetition is the dominant devices used.